Factors influencing nurses' job satisfaction in selected private hospitals in England - RP Lephalala (AOSIS, 2008)
The quantitative descriptive survey used self-completion questionnaires to study factors influencing nurses' job satisfaction in selected private hospitals in England. Herzberg's Theory of Motivation was used to contextualise the results obtained from 85 completed questionnaires.